Влияние колебаний и динамики климата на полупустынные ландшафты Северо-западного Прикаспия - Атаев (Ataev Zagir), Загир Вагитович; Братков (Ataev Vitaliy), Виталий Викторович (Географический вестник=Geographical bulletin, 2017)
В статье выявлены тренды изменения климатических условий и оценены изменчивость гидротермических условий в полупустынных ландшафтах Северо- Западного Прикаспия, вклад различных состояний и их групп во временнýю структуру полупустынных ландшафтов, охарактеризована сезонная и разногодичная динамика ландшафтов. THE IMPACT OF FLUCTUATIONS AND DYNAMICS OF CLIMATE IN THE SEMIARID LANDSCAPES OF THE NORTH-WESTERN CASPIAN The authors of the article reveal trends of climatic conditions’ changing and variability of hydro-thermal conditions in semi-desert landscapes of North-western areas of the Caspian coast, evaluate the different conditions’ contribution and their groups to the temporary structure of semi-desert landscapes, characterize landscape dynamics during different seasons and years.